Coastal tourism and fisheries nexus as a social-ecological system case studies of selected small islands in Western Visayas, Philippines. - Anasco, Cherry Pilapil
The natural resources in the coastal and marine environement have been an important source of food, goods and services of humans since time immemorial. However, an archipelagic country's small islands are being challenged by an increasing population who are dependent on the fish catch from the wild. To address such challenges, several schemes have been developed. One such scheme is coastal resource management (CRM) which will hopefully include coastal and fissheries tourism as a CRM strategy. This study therefore was conducted in the Western Visayas islands of Boracay, Gigantes and Guimaras to evaluate coastal tourism and fisheries nexus (CTF) through the lens of social-ecological system (SES) theoretical approach using the Driver-Pressure-Stale-Impact-Ressponse (DPSIR) framework of analysis. Fisher, management, tourism enterprise and visitor Delphi surveys were conducted in 2018-2019 to characterize and compare the three CTF sites as SES, to evaluate the CTF SES of the three islands using DPSIR approach with tourism as the main driver, to examine the resiliency of CTF SES, to analyze its sustainability, and to propose a management/policy framework as basis of decision towards sustainable tourism and resiliency for small islands. results show that human and ecological systems clearly interact in CTF with the steady increase of Actors. Resource systems in small islands include the fishing ground, coral reefs, seagrass beds, and mangrove forest while fish and other coastal organisms, island hopping, snorkeling, swimming and diving are among its resource units. Governance systems implemented by various institutions in the islands are covered by international, national and local laws and policies. Comparisons of islands show no significant difference between Boracay and Gigantes as CTF SES yet both are significantly different from Guimaras. DPSIR indicated increasing Pressure as more Actors are lured to the islands to take advantage of the provisioning or recreation ecosystem services form the resource systems, which supported supplemental/alternative livelihoods for fishers and other members of the community. Consequently, the State of the resource systems were affected with Impacts on both social and ecological subsystems. Interestingly, per Actor's perspective, stakeholder Responses to counteract impacts are favorable as shown by high natural and experience values of the CTF SES. The ecological sustainability values in the three islands however, were quite low as they are confronted with various natural and anthropogenic hazards, although hazard awareness was high. In addition, based on the indicators, Boracay and Gigantes islands are moderately resilient to disasters while Guimaras is extremely resilient to any disaster. Overall, findings reveal that the three small islands have acceptable performance towards achieving sustainable goals, with "potentially sustainable" status (i.e., goal almost achieved) for ecological and institutional dimensions and a "sustainable" status (.e., goal achieved) in the socio-economic dimension. These findings show that a balance between resource systems conservation and utilization in small islands is vital for coastal and fisheries tourism to be employed as a CRM strategy. A multi-sectoral, holistic and integrated approach should therefore be adopted in the management of small island tourist destinations with a sustainable tourism as a means to properly manage coastal resources, and consequently provide for the building of resilient small island communities.